2019
DOI: 10.18063/ijps.v6i1.1042
|View full text |Cite
|
Sign up to set email alerts
|

Voices of rural people: Community-level assessment of effects and resilience to natural disasters in Odisha, India

Abstract: Globally, natural disasters have caused a large scale of damage and destruction every year, affecting millions of people, the economy, and development – and developing countries are the most severely affected. Odisha is one of India’s most disaster-prone states. This study explores the effects of, and resilience to, cyclones, floods, droughts, and heatwaves in Odisha, and identifies government strategies that help mitigate these natural disasters. We mainly used primary data collected through a qualitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Further, these choices trap older adults in villages, without adequate financial means and family support, to pursue livestock management. A similar development was recorded in Odisha, where the youth migrated to urban areas (after natural disasters), leaving the older adults to fend for themselves (Patel, Mathew, Nanda, et al, 2020). Therefore, adaptation can involve intergenerational tensions as well as the sacrifice of short-term adaptive capacity to bolster long-term adaptive capacity.…”
Section: Discussionmentioning
confidence: 56%
“…Further, these choices trap older adults in villages, without adequate financial means and family support, to pursue livestock management. A similar development was recorded in Odisha, where the youth migrated to urban areas (after natural disasters), leaving the older adults to fend for themselves (Patel, Mathew, Nanda, et al, 2020). Therefore, adaptation can involve intergenerational tensions as well as the sacrifice of short-term adaptive capacity to bolster long-term adaptive capacity.…”
Section: Discussionmentioning
confidence: 56%
“…Unfortunately, the agriculture production ecosystem is widely affected by various climateinduced vulnerabilities. Many past studies have documented the same (Mishra, 2007;Chhotray and Few, 2012;GoO, 2016;Duncan, Tompkins, Dash, et al, 2017;Patel, Mathew, and Nanda, 2019;Patel, Mathew, Nanda, et al 2020). This vulnerability not only affects agriculture production systems but also impacts nutrition outcomes of the household in terms of creating a scarcity of food, particularly nutrient-rich quality food for the agriculturally dependent households.…”
Section: Discussionmentioning
confidence: 88%
“…Using 45 years of data for seven selected crops (panel data) of Odisha Das (2017) observed that changing climate, particularly at the rainfall and temperature level, has significant impacts on the crop production in Odisha (Das, 2017). Research studies using panel regression analysis found that climate change has a significant influence on the agriculture production system in Odisha (Mishra and Sahu, 2014;Mishra, Sahu and Sahu, 2015;Patel, Mathew, Nanda, et al, 2020). IPCC (2007) working Group-II estimates that changing climate in India will lead to a drop in wheat production by 4-5 million tones, 4-35% reduction in rice yields, and negative impacts on livestock (WG-II, IPCC-2007).…”
Section: Relationship Of Climate Vulnerability and Household Food And Nutrition Statusmentioning
confidence: 99%
“…Droughts have been linked to early marriage in certain settings, as families offset financial harms from crop loss by securing dowries [37][38][39] or reducing the number of mouths to feed. Droughts have also been linked with food insecurity [40][41][42], children joining families in the brick-kiln industry [43] and dropping out of school [44,45]. Rural agricultural households may be more likely to be harmed by droughts, resulting in economic and food insecurities.…”
Section: Discussionmentioning
confidence: 99%